2022
DOI: 10.25270/wnds/21089
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Treatment Utilizing an Autologous Blood Clot for Diabetic Foot Ulcers

Abstract: Introduction. Diabetic foot ulcer is a complex wound that requires considerable effort to restart a stalled healing process. In this study, a TABCT product was used in a point-of-care setting to treat DFUs by reconstructing the ECM and adjusting intricate phenotypes and mechanisms of mediators to progress towards complete healing. The mechanism of action consists of reconstruction of the ECM, which protects the wound area from further destruction while it incorporates into the ulcer to promote granulation over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Previous studies have demonstrated the safety and efficacy of this technology in treating challenging nonhealing cutaneous wounds [12][13][14][15][16][17] and complex surgical wounds. 33 Using autologous blood clots, which provide a transient scaffold and recruit surrounding cells to activate wound healing, 32 presents a promising strategy to treat open and chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the safety and efficacy of this technology in treating challenging nonhealing cutaneous wounds [12][13][14][15][16][17] and complex surgical wounds. 33 Using autologous blood clots, which provide a transient scaffold and recruit surrounding cells to activate wound healing, 32 presents a promising strategy to treat open and chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…12 The treatment was found to be safe and effective in acute and chronic soft tissue wounds. [13][14][15][16][17] The blood clot product is applied to the entire wound surface, thus creating a temporary scaffold and matrix to facilitate tissue healing. 18 In this study, we aimed to explore the safety and efficacy of RD2 ver.02 treatment for closure of simple and complex transsphincteric anal fistula.…”
Section: Limitacionesmentioning
confidence: 99%
“…A terapia tópica do coágulo sanguíneo autólogo (TTCSA), comercializado com nome de Actigraft ® , consiste em um coágulo de sangue total criado a partir de sangue periférico do próprio paciente, que atua como ambiente protetor, imitando as propriedades da matriz extracelular, promovendo diminuição da intensidade da dor através da modulação da inflamação. Este coágulo autólogo é capaz de converter macrófagos M1 em M2 que secretam citocinas anti-inflamatórias, progredindo a ferida para fase proliferativa da cicatrização, proporcionando desta forma um fechamento rápido e mais eficiente que o tratamento convencional (7,8) .…”
Section: Introductionunclassified